Genetic analysis in mango (Mangifera indica L.) based on fruit characteristics of 400 genotypes - Sankaran, M; Dinesh, M R; Gowda, D C S; Venugopalan, R (Journal of Horticultural Sciences, 2020)
The analysis of variance for 6 quantitative traits and 30 qualitative traits showed significant differences among the 400 genotypes of mango which indicates the existence of high heterozygosity. Among the 18 clusters formed, the highest fruit weight of 1404.27 g was recorded in cluster 10 followed by cluster 15 with 1280.67g whereas the lowest fruit weight was recorded in cluster 16 (30.94g). The highest fruit length (22.03 cm) was recorded in cluster 10 followed by 17.80 cm in cluster 14. Similarly, the fruit diameter was highest (12.18 cm) in cluster 10 followed by 12.03 cluster 4. The fruit thickness was highest (10.60 cm) in cluster 15 followed by cluster 4 with 9.96 cm. The pulp recovery was maximum (87.16%) in cluster-14 followed by clusters 4 and 18 with 79.28 and 78.41 %, respectively. Clusters 15 had the varieties meant for pickle making and possessed less TSS whereas the TSS of above 19°B was recorded in cluster 2. The maximum inter-cluster (D2) value was obtained between cluster 10 and cluster 11. These clusters may be used for hybridization programs due to wide variability and the possibility of transgressive sergeants. Estimates of phenotypic variance and genotypic variance had only a narrow difference for all six characters studied indicating that these characters are not much influenced by environmental factors and highly heritable which can be exploited by adopting clonal selection or selection of chance seedlings and selection as parents for breeding purpose.
Keywords: Biplot analysis; GCV; Genetic analysis; Heritability; Mango; PCV